OBSTACLES TO TEACHING MATHEMATICS AT THE PRIMARY STAGE FROM THE POINT OF VIEW OF EDUCATIONAL SUPERVISORS (American Journal of Pedagogical and Educational Research, 2023)
The aim of the research is to identify the obstacles to teaching mathematics in the primary stage from the point of view of educational supervisors in the schools of the second Iraqi city of Rusafa. In the light of the results of the study, the researcher recommended the need for good planning and preparation of training programs for mathematics teachers, and concerted efforts to overcome these obstacles, especially those related to mathematics books and evaluation methods.